Real time PPG data acquisition with GUI based application for HRV measurement - Zainal, Nur Izzati; Sidek, Khairul Azami (Indian Society for Education and Environment, 2016)
This paper presents a study of Photoplethysmography (PPG) for Heart Rate Variability (HRV) measurement. PPG is a non-invasive device which is used to measure the blood volume changes in the veins. Using optical based method, the PPG signal gives such reliable information regarding to the person’s body condition. One of the information that could be extracted from PPG signals is the measurement of HRV. In this research, PPG data acquisition is done in real time where it is directly processed using Graphical User Interface (GUI) based application. The main purpose of this research is to design a prototype for acquiring real time PPG signal for HRV measurement. Raw PPG data is extracted from HRM2511e and filtered using Easy Pulse circuit. Then, a software prototype is built for feature extraction and classification. The result is based on 6 different subjects. Each subject will provide PPG signal and HRV measurement in two different physical conditions which are sitting and standing.